P293 Loss of response after first-line biologic therapy in patients with inflammatory bowel disease: practical approach and management. (15th January 2020) - Busacca, A; Scrivo, B; Giuffrida, E; Guida, L; Carrozza, L; Calvaruso, V; Cappello, M
Abstract: Background: Anti-tumour necrosis factors (anti-TNFs) have greatly improved therapeutic strategies for the treatment of inflammatory bowel diseases (IBDs). However, a significant number of patients do not respond or lose response over time (LOR). The aim of this retrospective prospective study was to evaluate patients (patients) treated with anti-TNFs as first-line treatment, with subsequent LOR, defined as recurrence of disease activity during maintenance therapy. We determine the prevalence of LOR and its management. Methods: Three-hundred forty patients with IBDs were included: 65% had Crohn's disease and 35% ulcerative colitis. Mean age at diagnosis was 31, 5 years and medium time between diagnosis and start of biologic treatment was 72 months. Among 300 patients treated with anti-TNFs, LOR occurred in 33%, 38% was in treatment with Infliximab, 55% with Adalimumab, and 7% with Golimumab and it was statistically related with smoke ( p = 0.028), type of drug ( p = 0.001) and with the duration of treatment ( p = 0.019). Results: Among patients with LOR, 88% had a persistent clinical activity, evaluated by clinical scores (HBI and pMayo score) and 56% had a persistent endoscopic activity, evaluated by endoscopic scores (SES-CD and Mayo). After the LOR, 56% of patients optimised treatment for medium time of 7, 8 month, 31% switched to another Anti-TNF, 7% swapped to a different class of biologics (Vedolizumab or Ustekinumab) and 4% had surgery as a treatment strategy. During treatment with anti-TNF as second-line treatment, LOR occurred in 17 patients. Anti-TNFs was the third line therapy in 3 patients, while Vedolizumab in 13. Only 2 patients in treatment with Vedolizumab had a second LOR and started Ustekinumab. Conclusion: Loss of response occurred frequently in patients treated with biologics. Optimisation of treatment was not efficacious during a long period and the use of another biologic (anti-TNF or another class) is the more suitable strategy in our centre, with success in 35% of patients who lose response.